The Good Life with Dementia approach: A realist-informed qualitative study of a peer-tutored course, co-produced with and for people living with dementia - Kate Gridley; Mark Wilberforce; Rachel Mann; Laura Tucker; Beth Casey; Chris Clarke; Sam Creavin; Irene Donaldson; Howard Gordon; Damian Murphy; Mark Pearson; Mohammed Akhlak Rauf; et al. (PLoS ONE, 2026)
People with dementia often report a lack of post-diagnostic support, and much of the current dementia training available is for staff or carers, not for the person diagnosed. The Good Life with Dementia course was designed with and for people with a diagnosis of dementia and is co-delivered by peer-tutors living with dementia, supported by a trained facilitator. This study used realist-informed methods, underpinned by a co-productive ethos which values all sources of expertise equally, to better understand the core constructs underpinning the Good Life approach and how these operate to produce outcomes. The resultant, evidence-based programme theory suggests that – in a context characterised by shared experience, equality and positive expectations – three key mechanisms can trigger: sharing of experiences and resources; peer-led learning and responding; and the taking on of meaningful roles. Qualitative evidence indicates that these mechanisms are likely to lead to four interconnected outcomes: enjoyment; feeling valued (personhood); (re)building social confidence and connections; and positive reframing of life with dementia, meaning participants felt more prepared to face the challenges ahead. Not everyone diagnosed with dementia will want to take part in a peer-led course, but interventions like a Good Life with Dementia could be part of a suite of post-diagnostic options available to help people with dementia to live as well as possible. The next step will be to establish whether the approach can be manualised, delivered with different communities and evaluated in trial conditions. This will be assessed via an inclusive feasibility study already underway and due to conclude in August 2027.